2020
DOI: 10.1007/s10811-020-02155-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of irradiance, temperature, nutrients, and pCO2 on the growth and biochemical composition of cultivated Ulva fenestrata

Abstract: Ulva fenestrata is an economically and ecologically important green algal species with a large potential in seaweed aquaculture due to its high productivity, wide environmental tolerance, as well as interesting functional and nutritional properties. Here, we performed a series of manipulative cultivation experiments in order to investigate the effects of irradiance (50, 100, and 160 μmol photons m−2 s−1), temperature (13 and 18 °C), nitrate (< 5, 150, and 500 μM), phosphate (< 1 and 50 μM), and pCO2 (200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 65 publications
7
43
2
Order By: Relevance
“…Conversely, Gao, Clare, Chatzidimitriou, Rose, and Caldwell (2018) found that lipid (and protein) content increased at elevated nutrient levels. In line with these findings, U. fenestrata produced in defined tank cultivation increased the fatty acid and protein contents at high nitrate concentration and at low illumination (Toth et al, 2020). Reports also show positive effects of increased temperature (20-25°C) on lipid and protein contents, as well as lowered ash content for Ulva spp.…”
Section: Discussionsupporting
confidence: 75%
“…Conversely, Gao, Clare, Chatzidimitriou, Rose, and Caldwell (2018) found that lipid (and protein) content increased at elevated nutrient levels. In line with these findings, U. fenestrata produced in defined tank cultivation increased the fatty acid and protein contents at high nitrate concentration and at low illumination (Toth et al, 2020). Reports also show positive effects of increased temperature (20-25°C) on lipid and protein contents, as well as lowered ash content for Ulva spp.…”
Section: Discussionsupporting
confidence: 75%
“…For cultured or bioreactor-grown algae, changing the medium composition is a straightforward way to improve protein content. For instance, the increase of nitrogen, phosphate, and CO 2 seems enhance protein accumulation in algae (Kumari et al, 2014;Tossavainen et al, 2019;Toth et al, 2020). As an example, Tossavainen et al (2019) concluded that, in high-nitrate medium (0.5 g/L of ammonium sulfate), protein content of Euglena gracilis varied between 17.51 and 18.56% of dry weight, while under lower concentrations or absence of nitrogen (0.2 g and 0.0 g/L of ammonium sulfate, respectively), algal proteins in biomass ranged between 10.99 and 12.09% of dry weight.…”
Section: Strategies To Enhance Protein Contentmentioning
confidence: 99%
“…Given the worldwide guidelines pointing towards more sustainable and "greener" processes based on circular economy and zero-waste concepts, it is possible, for instance, to improve biomass and metabolites' productivity while treating industrial wastewater streams or taking advantage of the great organic load of agro-industrial by-products to supress the nutritional needs of algae (Kazir et al, 2019). In the particular case of algal proteins, it is known that the growth using nitrogen-or phosphorus-rich substrates might trigger their overproduction, enabling the potential application of the aforementioned underrated streams as means of increasing algae's protein content (Kumari et al, 2014;Tossavainen et al, 2019;Toth et al, 2020).…”
Section: Environmental Impact and Economic Prospects Of Algae Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the full exploitation of this technique, there is a need to develop cultivation methods from a multidisciplinary perspective. Preliminary cultivation studies can allow the control and understanding of the impact of extrinsic and intrinsic factors, in order to obtain a specific yield and quality of a certain seaweed compound, with a high rate of success, without putting pressure in the wild seaweed community while also reducing production costs [ 1 , 97 , 115 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ].…”
Section: Drivers To the Production Of Phenolic Compounds And Their Impact On Bioactivitymentioning
confidence: 99%